Some Generalized Gronwall-Bellman Type Impulsive Integral Inequalities and Their Applications - Yuzhen Mi (Journal of Applied Mathematics)
This paper investigates some generalized Gronwall-Bellman type impulsive integral inequalities containing integration on infinite intervals. Some new results are obtained, which generalize some existing conclusions. Our result is also applied to study a boundary value problem of differential equations with impulsive terms.